CURRENT PRACTICE OF INTRODUCTION OF COMPLEMENTARY FEEDING PRODUCTS: TO WHOM? WHEN? HOW MUCH? - Y. A. Dmitrieva; I. N. Zakharova; N. G. Sugyan; I. V. Berezhnaya (Медицинский совет, 2017)
The problem of introduction of complementary foods continues to be debated both in academic circles and among practitioners. The most relevant is the discussion on the optimal timing and sequence of the introduction of individual products, individual planning of the diet of children with food allergies, a possibility of using products of complementary foods in the complex treatment of functional digestive disorders and various deficient states, as well as the role of new products in the formation of eating behavior of the child. In the conversation the employees of the Department of Pediatrics of RMANPO chaired by Professor Irina Nikolaevna Zakharova tried to answer frequently asked questions regarding introduction of complementary foods to the infants.